Quiz Enhances Writing Skills in Descriptive Texts Among Students in Indonesia - Putri, Nurmansyah Eryka; Nuroh, Ermawati Zulikhatin (Inquest Journal, 2025)
This study investigates the impact of Quizizz media on the ability to write descriptive texts in class VIIIB at MTs. Al-Musthofa. Utilizing a pre-experimental design with one group pretest and posttest, 30 students from a total population of 126 were selected as the sample. Data were collected through written tests to assess students' writing skills. The analysis revealed a significant improvement in students' writing abilities when taught using Quizizz, with a sig (2-tailed) value greater than 0.05, indicating that the null hypothesis was accepted. Additionally, a positive influence of Quizizz on writing skills was observed, supported by a homogeneity value of 972. This study underscores the importance of integrating technology-based media like Quizizz to enhance creativity and foster an engaging learning environment, particularly for millennial students. The findings suggest that teachers should incorporate varied, technology-supported teaching methods to create a stimulating educational experience.